Workers' Voice: Workers' Voice in European corporate governance - an invitation to open up new perspectives for participatory democracy - Norbert Kluge; Robin Leger; Maxi Leuchters (Hans-Böckler-Stiftung, Institut für Mitbestimmung und Unternehmensführung (I.M.U.), 2019)
Mitbestimmungsreport No. 52 summarises the results of the Böckler group of experts' "Workers' Voice" and shows that various forms of the Workers' Voice are distributed in Europe - as functional equivalents with similar features and objectives: representing workers' interests, protecting and enforcing workers' rights, and being proactively involved in management decisions. To enable Workers' Voice to play a major role for a social Europe, the EU must revise the European legal framework and strengthen good corporate governance. This includes enshrining co-determination in supervisory and management boards of multinationals in a legally binding way, protecting existing rights to participate on a national level, and stipulating minimum standards for information, consultation and co-determination.
Keywords: 330